2011
DOI: 10.1007/s12031-011-9623-2
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Expression of Enkephalinase and Aminopeptidase N in Regions of the Mesocorticolimbic System are Selectively Modified by Acute Ethanol Administration

Abstract: Opioid peptides play a key role in ethanol reinforcement and alcohol drinking behavior. However, regulation of opioid levels by peptidase-degrading activities in ethanol's actions in brain is still unclear. The aim of this work was to study the acute effects of ethanol (2.5 g/kg) on enkephalinase (NEP) and aminopeptidase N (APN) activities and expression in regions of the mesocorticolimbic system, as well as on corticosterone levels in serum for up to 24 h after administration. Enzymatic activities were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Earlier studies have demonstrated rapid degradation of opioid peptides by any of 5 types of peptidase: 1) aminopeptidase N (EC 3.4.11.2), which cleaves the Tyr 1 -Gly 2 amide bond; 2) dipeptidyl peptidase III (EC 3.4.14.4), which hydrolyzes the Gly 2 -Gly 3 bond; 3) dipeptidyl carboxypeptidase (EC 3.4.15.1, also known as the angiotensin I-converting enzyme); 4) neutral endopeptidase (EC 3.4.24.11, also known as enkephalinase), which cleaves the Gly 3 -Phe 4 bond; and 5) carboxypeptidase A (EC 3.4.17.1) (Khaket et al, 2012;Morales-Mulia et al, 2012). The membrane-bound three enzymes, aminopeptidase N (APN), dipeptidyl carboxypeptidase, and neutral endopeptidase (NEP), play an essential role in the degradation of [Met 5 ]enkephalin (ME) in three different types of isolated preparation: guinea pig ileum (Aoki et al, 1984), mouse vas deferens (MVD) (Aoki et al, 1986) and rat vas deferens (Cui et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have demonstrated rapid degradation of opioid peptides by any of 5 types of peptidase: 1) aminopeptidase N (EC 3.4.11.2), which cleaves the Tyr 1 -Gly 2 amide bond; 2) dipeptidyl peptidase III (EC 3.4.14.4), which hydrolyzes the Gly 2 -Gly 3 bond; 3) dipeptidyl carboxypeptidase (EC 3.4.15.1, also known as the angiotensin I-converting enzyme); 4) neutral endopeptidase (EC 3.4.24.11, also known as enkephalinase), which cleaves the Gly 3 -Phe 4 bond; and 5) carboxypeptidase A (EC 3.4.17.1) (Khaket et al, 2012;Morales-Mulia et al, 2012). The membrane-bound three enzymes, aminopeptidase N (APN), dipeptidyl carboxypeptidase, and neutral endopeptidase (NEP), play an essential role in the degradation of [Met 5 ]enkephalin (ME) in three different types of isolated preparation: guinea pig ileum (Aoki et al, 1984), mouse vas deferens (MVD) (Aoki et al, 1986) and rat vas deferens (Cui et al, 1986).…”
Section: Introductionmentioning
confidence: 99%